Identifying recreational fisheries in the Mediterranean Sea through social media. (28th June 2018) - Giovos, Ioannis; Keramidas, Ioannis; Antoniou, Charalampos; Deidun, Alan; Font, Toni; Kleitou, Periklis; Lloret, Josep; Matić‐Skoko, Sanja; Said, Alicia; Tiralongo, Francesco; Moutopoulos, Dimitrios K.
Abstract: The impact of recreational fishing on fish stocks remains largely unknown, as this is inherently difficult to monitor, especially in areas such as the Mediterranean Sea where many species are targeted using a variety of fishing gears and techniques. This study attempts to complement existing data sets and construct the profile of recreational fisheries in the EU‐Mediterranean countries using videos publicly available on social media. A total of 1526 video records were selected, featuring the capture of 7799 fish specimens. The results show recreational fishing is multispecies in nature (26 species contributed to >80% % of the most numerically important species caught) and exhibits a spatially homogeneous pattern, with differences in species composition being mostly dependent on the fishing technique used rather than on the country. Such findings fill an important knowledge gap on recreational fishing activities, and the methodology provides an innovative approach to gather statistics on data‐poor thematic areas that can potentially complement other data sets, such as the EU Data Collection Multi‐Annual Programme.